Effect of phosphorus and plant growth regulators on growth and yield of fenugreek (Trigonella foenum-graecum L.) - S S Rathore, R P S Shaktawat, Ruchita Gour, I S Naruka, P P Singh, (Journal of Spices and Aromatic Crops, 2009)
A field experiment was conducted at Mandsaur (Madhya Pradesh) to find out the effect ofphosphorus and plant growth regulators on growth and yield of fenugreek (Trigonellafoenum-graecum). The results indicated that significantly higher growth and yield (17.62 qha-1) were observed with application of 60 kg phosphorus ha-1. Foliar spray of naphthaleneacetic acid (NAA) 20 ppm at 25 days after sowing (DAS) and 55 DAS resulted in significantlyhigher growth and seed yield (17.41 q ha-1). The highest benefit : cost ratio (4.20:1) wasobserved for the treatment, 60 kg phosphorus ha-1 + NAA 20 ppm.